DINAMIKA PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK DISABILITAS INTELEKTUAL DI SEKOLAH DASAR INKLUSIF - Abd. Gofar; Devy Habibi Muhammad (LPPM STAI Muhammadiyah Probolinggo, 2026)
The implementation of Islamic Religious Education (IRE) for students with intellectual disabilities in inclusive schools requires instructional practices that are tailored to their individual characteristics and learning needs. However, studies that comprehensively examine students' abilities, learning needs, instructional practices, implementation challenges, and effective learning strategies remain limited. This study aimed to analyze the abilities and learning needs of students with intellectual disabilities in Islamic Religious Education and to formulate effective instructional strategies at SD Muhammadiyah Plus Probolinggo. This research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, Islamic Religious Education teacher, classroom teacher, shadow teacher, two students with intellectual disabilities, and their parents. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data credibility. The findings indicate that students' learning needs encompass cognitive, affective, and psychomotor domains, requiring curriculum modification, simplified learning materials, concrete instructional media, repetitive learning activities, and individualized support from shadow teachers. Although the school's instructional practices have accommodated these needs, several challenges remain, including cognitive limitations, emotional regulation difficulties, and students' adaptive skills. The study concludes that the effectiveness of Islamic Religious Education is determined by individualized instruction, the competence of shadow teachers, and sustained collaboration among schools, parents, and related professionals to optimally support students' development.